Evaluation of The Stability of Nitrogen-Fixing Bacterial Co-cultures under Different Cultivation Conditions - Syaadah,Wida (2025)
The Haber-Bosch process is a widely used method for industrial nitrogen fixation, converting nitrogen gas (N₂) into ammonia (NH₃). However, it is energy-intensive, requiring high temperatures and pressures. Biological nitrogen fixation (BNF) may offer a sustainable alternative, utilizing bacteria like Azotobacter vinelandii to convert nitrogen gas into ammonia. Co-culture systems combining A. vinelandii with microorganisms like Pseudomonas putida could support nitrogen-dependent bioproduction. A. vinelandii showed that it can grow and produce ammonium in both Burk’s medium and M9 medium without ammonium supplementation, although the microorganism requires more time adaptation in M9 medium without ammonium. Furthermore, the bacteria can produce more ammonium in stationary phase without carbon sources. Below 1.25 mM of ammonium, P. putida has a slow growth rate, while in supplementation of 5 mM of ammonium P. putida has the highest growth rate. Two cultivation strategies were evaluated for the ability of P. putida to proliferate using ammonium produced by A. vinelandii. First, a sequential growth strategy was evaluated, where P. putida sustain growth in spent medium from A. vinelandii supplemented with glucose and trace elements. Secondly a simultaneous growth strategy was evaluated, in which a mix of A. vinelandii and P. putida formed a synthetic co-culture. Using flow cytometry and plate count methods, it was found that both strategies are possible, and that P. putida indeed could proliferate using ammonium supplied by A. vinelandii.
Keywords: A. vinelandii; P. putida; ammonium; co-culture; flow cytometry; applied microbiology